Enrollment Equitable for UPTC - González, Jorge Iván; Martínez, Jorge; Mendoza, Andrés; Reverón, Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The article proposes a new tariff for paying tuition UPTC. The formula has these characteristics: 1) Ses the recovery taking account socio-economic capabilities of students and not according to the career, 2) Keeps the total amount of revenue received by the university fromtuition fees, 3) It is equitable because peoplewith lower income pay relatively less, 4)Does not affect current structure of household consumption.The design of the tariff wasmade after reviewing the formulas of other public universities, and to examine the characteristics socioeconomic families of those admitted to in the context UPTC general household surveys